2016
DOI: 10.1103/physrevb.93.235141
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of bidirectional charge-density waves inErTe3

Abstract: We report a strong difference in the sliding properties of the bidirectional charge density wave (CDW) in the two-dimensional rare earth tritelluride ErTe3 which occurs below TCDW 1 = 265 K with a wave vector along c-axis and below TCDW 2 = 165 K with a wave vector along a-axis; the excess current carried by the motion of the CDW is 10 times less for the lower CDW compared with the value of the upper one. We tentatively explain this result by a stronger pinning of the lower temperature CDW intricated with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…The voltage changes linearly with the increase of current at different temperatures, which indicates SnS 2 is a pure metal state under 39.2 GPa. No saturation voltage or regular fluctuation related to charge density waves was found in the differential resistance, d V /d I . , …”
mentioning
confidence: 85%
“…The voltage changes linearly with the increase of current at different temperatures, which indicates SnS 2 is a pure metal state under 39.2 GPa. No saturation voltage or regular fluctuation related to charge density waves was found in the differential resistance, d V /d I . , …”
mentioning
confidence: 85%
“…They are all expected to occur at the mesoscopic scale, i.e., comparable to the CDW domain sizes that are often much greater than the density-modulation periodicity. Unfortunately, the majority of experiments carried out to date for addressing disorder effects in CDW materials fall either into the macroscopic regime, such as transport and thermodynamic measurements [27][28][29] , or into the atomic-scale regime, such as scanning probe experiments 30,31 .…”
mentioning
confidence: 99%
“…In the incommensurate CDW system, extremely large polarization effects are expected due to weak pinning from impurities or defects [51]. For the CCDW state in 1T-TaS 2 , unlike the incommensurate 2D-system TbTe 3 where Sinchenko et al observed CDW sliding [25], for it would be difficult to slide in a moderate electric field due to the strong pinning by the underlying lattice and hence the contribution to the static dielectric constant would be much smaller [51]. Here one may argue that the mechanism in establishing the colossal dielectric constant in (NbSe 4 ) 3 I (due to the slight shift of the single chains against each other) can be a potential substitute for 1T-TaS 2 , however, such similar features of the lattice structure has not been identified yet [10].…”
Section: Resultsmentioning
confidence: 99%
“…The 2D-CDW often reveals itself in layered transition-metal dichalcogenides and rareearth tritellurides [13,14,[23][24][25][26]. Researchers began to study the charge transport properties of 2D-CDW systems (1T-TaS 2 ) about forty years ago: Refs.…”
Section: Introductionmentioning
confidence: 99%